Transformasi Dakwah: Urgensi Dakwah Digital di Tengah Pandemi Covid-19 - M. Khamim (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2022)
The Covid-19 pandemic has caused major changes to the order of people's lives and has become a real threat to human life, namely threats to the economic sector, education, culture, worship practices, and also da'wah activities. In da'wah activities, the construction of da'wah, which has been carried out face-to-face in a majelis, must be carried out online as a result of physical and social distancing policies. This is where new media plays a very important role for da'wah subjects (da'i) in preaching. Currently, there are many leaflets on the schedule of routine recitations which are carried out through live streaming of various media platforms with Ngaji Online. Practically, da'wah has undergone a transformation from face-to-face offline to online. Through a descriptive qualitative approach to literature study, this paper reviews the process of transforming da'wah and the urgency of online media in da'wah activities during the COVID-19 pandemic. The purpose of the discussion in this paper is to find out the paradigm shift in da'wah and the role of online media platforms in supporting the implementation of da'wah during the pandemic. The results of the study found that the new pattern that was born by the contact of the kiai or da'i with social media in da'wah activities formed a new habitus or habit. Pesantren which were originally closed to the outside world, are now starting to present themselves to the general public through the study of the kitab kuning in the social media.